ANALYSIS INTELLECTUAL CAPITAL TRANSPORTATION COMPANIES IN INDONESIA STOCK EXCHANGE - Anisa, Anisa; Santosa, Herlambang Pudjo (Cerdika: Jurnal Ilmiah Indonesia, 2023)
This study aims to determine the effect of industry type, profitability, and leverage on Intellectual Capital in transportation companies listed on the Indonesia Stock Exchange. A total of 43 transportation companies listed on the Indonesia Stock Exchange were included in the study population from 2018 to 2021. Multiple linear regression data analysis yielded the following findings: Leverage has an effect on Intellectual Capital . Profitability has no influence on Intellectual Capital. The type of industry has an influence on Intellectual Capital